HIERARCHIES AND NETWORKS: TECHNOLOGICAL LIMITS OF SOVEREIGNTY - Isaev, Igor; Kornev, Arkadiy; Lipen, Sergey; Zenin, Sergey (Revista Inclusiones, 2020)
The article is concerned with the impact of the technological revolution on state and legal structures of society. This study aims at revealing the historical process of transforming hierarchical power structures into network power configurations. It focuses on the issues of sovereignty and nationhood as the crucial power-technological elements of the past and modern times. Being a postmodern structure of social management, a network affects all aspects of social life and develops a new understanding of normativity, domination and centralization. The introduction of the network approach into political and legal science requires a revision of such a traditional concept as sovereignty.